Post-thyroidectomy hypocalcemia exacerbated by chyle leak - Alzaman, Naweed (Endocrinol Diabetes Metab Case Rep, 2015)
Transient hypocalcemia after thyroidectomy is not uncommon and the risk increases with the extent of neck surgery. We report a case of severe and prolonged hypocalcemia after total thyroidectomy complicated by thoracic duct injury. Hypoparathyroidism and thoracic duct injury are potential complications following total thyroidectomy with extensive lymph node dissection. This case suggested that having both conditions may complicate treatment of hypoparathyroid-induced hypocalcemia by way of losses of calcium and vitamin D in the chyle leak. LEARNING POINTS: This report highlights chyle leak as an uncommon cause of prolonged hypocalcemia in patients who have undergone extensive neck surgery. Chyle has an electrolyte concentration similar to that of plasma. Medical treatment options for a chyle leak include fat-free oral diet or parenteral nutrition without oral intake, pharmacological treatment (primarily octreotide).